2014
DOI: 10.1021/jp501167f
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical Implications of Sphingosine Accumulation in Membrane Properties at Neutral and Acidic pH

Abstract: Sphingosine (Sph) is a simple lipid involved in the regulation of several biological processes. When accumulated in the late endosomal/lysosomal compartments, Sph causes changes in ion signaling and membrane trafficking, leading to the development of Niemann-Pick disease type C. Little is known about Sph interaction with other lipids in biological membranes; however, understanding the effect of Sph in the physical state of membranes might provide insights into its mode of action. Using complementary establishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 54 publications
(111 reference statements)
4
33
2
2
Order By: Relevance
“…The ordering effect of sphingosine on fluid PC membranes or on PC/sphingomyelin/cholesterol raft-mimicking membranes was shown to depend on sphingosine concentration and on pH. Gel domains enriched in sphingosine were more easily formed at neutral pH where most of sphingosine molecules are uncharged [46]. Model membranes were shown to be permeabilized by sphingosine [47] and the extent of permeabilization was shown to depend on the lipid composition.…”
Section: Model Membrane Permeabilization By Sphingosinementioning
confidence: 99%
“…The ordering effect of sphingosine on fluid PC membranes or on PC/sphingomyelin/cholesterol raft-mimicking membranes was shown to depend on sphingosine concentration and on pH. Gel domains enriched in sphingosine were more easily formed at neutral pH where most of sphingosine molecules are uncharged [46]. Model membranes were shown to be permeabilized by sphingosine [47] and the extent of permeabilization was shown to depend on the lipid composition.…”
Section: Model Membrane Permeabilization By Sphingosinementioning
confidence: 99%
“…We have also shown that sphingosine kills bacteria at rather low concentrations [18]. Further biophysical studies show that sphingosine and ceramide interact in the same membrane domains [22,23]. It is therefore tempting to speculate, although unproven that the "ceramide coat" of the bacteria might interact with sphingosine and might protect them from the bactericidal effect of sphingosine present in the luminal membranes of the enterocytes.…”
Section: Discussionmentioning
confidence: 89%
“…In addition, to further show the importance of developing adequate synthetic systems to address lipid-lipid interactions, comparison with standard vesicles (without pH gradient across the membrane) prepared under neutral, i.e., pH 7.4 in /7.4 out , and acidic, pH 5.0 in /5.0 out , conditions, was performed (Fig. 1), based both on new as well as available literature data 26 .…”
Section: Resultsmentioning
confidence: 99%
“…To test whether this experimental set up would compromise the stability of the vesicles altering its size, and to evaluate if the expected changes in surface charge were taking place upon changing the outer membrane pH from an acidic to a neutral environment 26 , analysis of vesicle size and surface charge was performed before and after separating the vesicles through the chromatographic column (Fig. 2) The ζ-potential of the ternary POPC/SM/Chol mixtures before size exclusion chromatography (i.e., when displaying pH 5.0 in /5.0 out ) was slightly positive, as expected since these lipid mixtures are at pH of 5.0 26 . A change in ζ-potential towards slightly negative values was observed upon creation of the pH gradient across the bilayer (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation